2021
DOI: 10.3390/medicina57020082
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Massive Spontaneous Pneumothorax—A Rare Form of Presentation for Severe COVID-19 Pneumonia

Abstract: Background and Objectives: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is a viral disease that is spreading worldwide and became a pandemic. Although most of the time, the symptoms of the infection are flu like, a percentage of patients develop severe forms, along with severe complications. Many of them are known among front-line health workers, but the number of uncommon presentations and complications has increased. This case report ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Its prevalence, risk factors, and final outcome remain unclear. 13,14,[30][31][32][33][34][36][37][38][39] Our research contributes to understanding the combination of SP, SPM and COVID-19 in non-ventilated patients, and quantifying their associated risks for in-hospital mortality.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Its prevalence, risk factors, and final outcome remain unclear. 13,14,[30][31][32][33][34][36][37][38][39] Our research contributes to understanding the combination of SP, SPM and COVID-19 in non-ventilated patients, and quantifying their associated risks for in-hospital mortality.…”
mentioning
confidence: 94%
“…6,8,11 It correlated with the severity of lung damage, rather than with the magnitude of SP-SPM. [12][13][14] However, a multicenter retrospective case study by Martinelli et al 7 challenged these findings, reporting an overall survival rate of 63.1% in patients confirmed with COVID-19 and SP. 7 We conducted a one-year review of the medical records in the emergency departments (ED) of two tertiary hospitals: Emergency Clinical Municipal Hospital and "Pius Brinzeu" Emergency Clinical County Hospital, both teaching hospitals affiliated with Victor Babes University of Medicine and Pharmacy in Timisoara.…”
Section: Introductionmentioning
confidence: 99%
“…There are increased reports of spontaneous pneumothorax in patients within the literature, which were thought to be an uncommon sequela of the infection. However, the development of the complication is not well understood, with some sources citing the virus as the cause while others are implicating pneumonia, poor intubation technique, or barotrauma [4][5][6][7]. In cases without proof of barotrauma, a secondary spontaneous pneumothorax may develop in the context of COVID-19 in 1% of patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…PSP is frequent in young people, with men having a higher frequency than women (7.4-18 per 100.000 men and 1.2-6 per 100.000 women). Being a male, having a slim and tall stature, and smoking are all risk factors (5). Some studies observed that PSP in COVID-19 pneumonia is usually associated with hypertension (37.5%), asthma (20%), and diabetes (17.5%), none of which were present in our patient (6).…”
Section: Discussionmentioning
confidence: 56%